Determination of composition, melting heat and the crystallinity degree of polyamide phase in polyamide-6/barium titanate system = Wyznaczanie składu kompozytu oraz ciepła topnienia i stopnia krystaliczności fazy poliamidowej w układzie: poliamid-6/tytanian baru - Gąsiorek, Marek; Jerzyniak, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The method of determination of ceramics contents and melting heat of polymer phase in composite PA-6/BaTiO3 has been suggested. Samples of composite have been obtained by polymerization of caprolactam in which the fine particles of barium titanate were dispersed. The obtained samples have been characterized by means of specific volume measurements and the DSC technique. Contents of barium titanate and melting heat of polyamide phase have been calculated using suitable equations.
Keywords: kompozyt; polimeryzacja; krystalizacja; compisite materials; composition of polyamide-ceramics composites